Effective Recruitment and Selection Aspects at Apotek D'Farma - Evi Silvana Muchsinati; Rano Ardiansyah (Universitas Internasional Batam, 2024)
Apotek D'Farma is a store that provides medicines, health products, and pharmaceutical services located at Ruko Bukit Kemuning DD 2 No.7 Mangsang, Batam, Riau Islands with 11 employees. The purpose of establishing this pharmacy is to ensure that every patient can effectively, safely, comfortably, and timely access the medicines they need. Currently, Apotek has a problem with a shortage of proper employees because it will expand the doctor's office. Because collaboration between pharmacies and physician practices can yield significant benefits for patients and businesses. In addition, there are competitors from other adjacent pharmacies so that employees who have competence and expertise in the field of medicine are needed. Based on the above problems, the recruitment and selection process is very necessary, so that the pharmacy will get the expected employees in accordance with their competence